70 - 80 - 90 en el Museo Nacional de Bellas Artes : Setenta artistas de la décadas del ochenta y noventa por Jorge Glusberg. - Glusberg, Jorge; O'Donnell, Mario (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1996)
Risso, Enrique Burone ; Houghton, Marcelo ; Scafidi, Roberto ; Tenenbaum, León ; Antoniadis, Carolina ; Aisenberg, Diana ; Mirocznyk, Gabriel ; Eckell, Ana ; Sturgeon, Richard ; Schvartz, Marcia ; Pierri, Duilio ; Fazzolari, Fernando ; Médici, Eduardo ; Kuitca, Guillermo ; Armentia, Gustavo Lopez ; de Sagastizábal, Tulio ; Bianchedi, Remo ; Crespo, Carlos Manuel ; Causa, María ; Dompé, Hernán ; Schnitman, Jorge ; Orta, Jorge ; Páez, Oscar ; Corujeira, Alejandro ; Hoffmann, Eduardo ; Landen, Patricia ; Macchi, Jorge ; Monzo, Osvaldo ; Socolovsky, Paula ; Spinosa, Santiago ; Bertani, Ernesto ; Doffo, Juan ; Garnica, Jorge ; Garcia, Daniel ; Médici, Héctor ; Aro, Elizabeth ; Lecuona, Juan ; María, Marino Santa ; Kacero, Fabio ; Finochietti, María ; Siquier, Pablo ; Conte, Guillermo ; Elía, Roberto ; Harte, Miguel ; Rivas, Silvia ; Pombo, Marcelo ; Zabala, Horacio ; Serra, Oscar ; Prior, Alfredo ; Rearte, Armando ; Romeo, Jorge ; Maza, Zulema ; Jezik, Enrique ; Marcaccio, Fabian ; Aranovich, Claudia ; Aslan, Nora ; Boullosa, Marcelo ; Gravinese, Diego ; Garófalo, José ; Alvarez, Eduardo ; Esnoz, Manuel ; Nigro, Miguel Angel ; Soria, Pablo ; Ballesteros, Ernesto ; Aphalo, Daniela ; Cánovas, Fernando ; Moujan, Marcela ; Reyna, Martin ; Hasper, Graciela ; Bruzzone, Dino
Spaans
boek